Analysis of Implementing Table Top Exercise and Command Post Exercise of Disaster Emergency Response - Bagus Tjahjono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
One of the important elements to reduce disaster risk is to increase preparedness to face disaster emergency response through simulation exercises. The purpose of this study was to analyze 9 (nine) aspects of implementing Table Top Exercise (TTX) and Command Post Exercise (CPX), namely participants; exercise scenario development; exercise stages; elements, roles, and functions; exercise planning products; exercise implementation mechanism; movement of TTX; movement of CPX and evaluation of the implementation of the exercise. The study involved 6 (six) Provincial BPBDs who carried out TTX and CPX for disaster emergency response in 2020. The approach used in this study was a qualitative method. Data collection techniques used were observation, discussion, and documentation with primary and secondary data sources. The results showed that 9 (nine) aspects of implementing exercise had been carried out comprehensively in accordance with the rules, methods, and procedures. The disaster preparedness training process through this exercise had been going well at the BNPB Disaster Management Training Center.